PSIKOLOGI SANTRI USIA DINI - Siti Mumun Muniroh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This study describes the psychological dynamics of Pesantren Salafiyah Syafiiyah Pekalongan early childhood students, which focused on their parenting, cognitive development, emotional and social behavior. Qualitative research data was obtained by interview, observation and documentation. The results of this study reveal: (1) caregivers parenting style were both on authoritarian and democratic. (2) types of parenting and child motivation on boarding school contribute to cognitive and psychosocial development of the child. Students who split up his guardian, and cared for on semi-authoritarian way will be less reasoning person, slow psychomotor skills, and less socialize. In contrast to students whom their parents support them and want their children to be good at lessons will master general science, able to memorize the Koran, and be better person.